Human Capital Strategic dan Dampaknya terhadap Kinerja Karyawan: Pendekatan Literature Review - Iznillah, Muhammad Luthfi; Julita (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2024)
Human Capital is the main capital of the organization in supporting the achievement of organizational performance. Changes in the world of work and economic conditions make Human Capital an interesting thing for organizations. Every organization seeks to optimize the potential of its human resources in order to achieve organizational goals, so that appropriate steps and strategies are needed regarding the application of Human Capital. The purpose of writing this article is to explore and summarize the literature review related to human capital in the company. so that it can find out alternative strategies that can be done by companies in order to improve employee performance. This article uses a literature review approach. The results of the literature review can be conveyed by researchers that, Human Capital Management is a top priority to improve employee performance. The company must be able to maintain and improve the Human Capital system and strategy, there needs to be a good strategy in building human capital such as by including company goals in line with employee goals and involving employees in every decision making. Employees are more likely to stay with organizations that have the same values and goals as them. The results of this study should be taken into consideration for companies in implementing Human Capital strategies as an effort to build a good organizational climate, so that it has an impact on employee performance achievements which indirectly also have an impact on competitive and sustainable company growth.